A thank you to DMM's peer reviewers - Rachel Hackett (The Company of Biologists, 2019)
The staff and editors of Disease Models & Mechanisms (DMM) wish to thank all our peer reviewers for their work in this vital role. We highlight some important changes that have been introduced to improve the peer-review process, for both authors and reviewers.